Article review: Brazilin as potential anticancer agent - Raptania, Callista Najla; Zakia, Syifa; Fahira, Alistia Ilmiah; Amalia, Riezki (Frontiers in Pharmacology, 2024)
Brazilin is the main compound in Caesalpinia sappan and Haematoxylum braziletto, which is identified as a homoisoflavonoid based on its molecular structure. These plants are traditionally used as an anti-inflammatory to treat fever, hemorrhage, rheumatism, skin problems, diabetes, and cardiovascular diseases. Recently, brazilin has increased its interest in cancer studies. Several findings have shown that brazilin has cytotoxic effects on colorectal cancer, breast cancer, lung cancer, multiple myeloma, osteosarcoma, cervical cancer, bladder carcinoma, also other cancers, along with numerous facts about its possible mechanisms that will be discussed. Besides its flavonoid content, brazilin is able to chelate metal ions. A study has proved that brazilin could be used as an antituberculosis agent based on its ability to chelate iron. This possible iron-chelating of brazilin and all the studies discussed in this review will lead us to the statement that, in the future, brazilin has the potency to be a chemo-preventive and anticancer agent. The article review aimed to determine the brazilin mechanism and pathogenesis of cancer.